Noncontiguous finished genome sequence and description of Prevotella phocaeensis sp. nov., a new anaerobic species isolated from human gut infected by Clostridium difficile. (January 2017) - Afouda, P.; Ndongo, S.; Khelaifia, S.; Labas, N.; Cadoret, F.; Di Pinto, F.; Delerce, J.; Raoult, D.; Million, M.
Abstract: Prevotella phocaeensis sp. nov. strain SN19 T (= DSM 103364) is a new species isolated from the gut microbiota of patient with colitis due to Clostridium difficile . Strain SN19 T is Gram-negative rod-shaped bacteria, strictly anaerobic, nonmotile and non–endospore forming. The predominance fatty acid is hexadecanoic acid. Its 16S rRNA showed a 97.70% sequence identity with its phylogenetically closest species, Prevotella oralis . The genome is 2 922 117 bp long and contains 2486 predicted genes including 56 RNA genes.